Substansi Evaluasi Pendidikan dalam Perspektif Pendidikan Islam - Fitriani Rahayu (Al-Ishlah: Jurnal Pendidikan Islam, 2019)
Islamic education aims to develop the natural potential in humans to become human beings. So that, all components in education must be accordance with the objectives of Islamic education. To find out the goal is achieved, evaluation is needed. This study uses literature studies by examining several books and leaders' thoughts, researchers will discuss more deeply about the evaluation of Islamic education both epistemology, terminology, axiology, and ontology. Evaluation can be interpreted as an effort to determine the level of success and weakness from Islamic education process, that covers all the components in it to achieve the stated goals. In the process of implementing the evaluation must apply several principles, techniques and procedures that must be followed for the good results to be obtained.